The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1057/palgrave.ejis.3000358
|View full text |Cite
|
Sign up to set email alerts
|

Perceived critical mass effect on groupware acceptance

Abstract: Groupware technologies have become an important part of the business computing infrastructure in many organizations, but many groupware applications, especially those requiring significant collaboration and cooperation among users, are still not adequately used. While the successful implementation of groupware depends on many different factors, achieving a 'critical mass' of users has been recognised as the key for groupware acceptance. By extending the technology acceptance model (TAM), this paper advances a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
169
2
10

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(190 citation statements)
references
References 35 publications
9
169
2
10
Order By: Relevance
“…Li et al [6] argued that the benefit of using a communication technology, such as IM, cannot be achieved by an individual if his or her communication partners do not use the technology. This is congruent with Lou et al [43] in that IS acceptance requires the participation of many individuals to create a sense of collective action and few people are willing to use technology on their own or in small numbers. This indicates that the use of technology will decline if critical mass is absent.…”
Section: Theory Of Critical Masssupporting
confidence: 73%
See 1 more Smart Citation
“…Li et al [6] argued that the benefit of using a communication technology, such as IM, cannot be achieved by an individual if his or her communication partners do not use the technology. This is congruent with Lou et al [43] in that IS acceptance requires the participation of many individuals to create a sense of collective action and few people are willing to use technology on their own or in small numbers. This indicates that the use of technology will decline if critical mass is absent.…”
Section: Theory Of Critical Masssupporting
confidence: 73%
“…This contention implies that critical mass is the basis for producing collective actions [43]. Prior studies suggested that theories in social psychology, economics, and diffusion of innovations all support that critical mass, by means of increasing interconnections amid users, is important for individual choices and actions [6,28,43].…”
Section: Perceived Connectivitymentioning
confidence: 99%
“…Unlike individual technology, which aims to improve individual productivity, group technology (groupware) aims to facilitate group coordination and to support cooperation and collaboration among a group of users. User acceptance of groupware is therefore different from that of individual technology due to the unique features of groupware (Lou et al, 2000). SN's effects may be different for individual technologies such as word processing software and group technologies such as email or v-mail.…”
Section: Individual Vs Group Technologiesmentioning
confidence: 99%
“…They argued that word processing was fairly personal and individual and may be driven less by social influences compared to other technologies such as email, project management or group decision support systems, and therefore, SN may have less effect in such technological contexts . Users who have adopted the technology have the incentive to enlist more users for the technology, and they may be eager to promote the technology by sharing their experience with and offering help to potential adopters (Lou et al, 2000). Such unsolicited help from many peers due to the unique features of groupware may convince a potential user that it would not take a lot of time and effort to learn and use the groupware, which promotes their intention to use it.…”
Section: Individual Vs Group Technologiesmentioning
confidence: 99%
“…In addition to the fact that the value of network goods (such as fax, phone or MSN Messenger) per definition increases with the number of users, Shapiro and Varian (1999) also argue that there is a strong perception of safety in numbers: Few people are willing to use a technology or service on their own or in small numbers. By the same token, Lou, Luo and Strong (2000) argue that adoption of information systems requires the participation of many individuals to create a sense of collective action.…”
Section: Theoretical Backgroundmentioning
confidence: 99%